Experimental Investigation of the Near-Surface Flow Dynamics in Downburst-like Impinging Jets Immersed in ABL-like Winds - Federico Canepa; Massimiliano Burlando; Horia Hangan; Djordje Romanic (Atmosphere, 2022)
Downburst winds are strong downdrafts of cold air that embed into the atmospheric boundary layer (ABL) and produce intense horizontal outflow upon impingement on the ground. They are highly transient and three-dimensional extreme wind phenomena with a limited spatiotemporal structure that often makes the anemometric measurements in nature inadequate for reconstructing their complex flow fields. In the framework of the project THUNDERR, an experimental campaign on downburst outflows has been carried out at the WindEEE Dome at Western University, Canada. The present study analyzes the three-dimensional interaction between downburst (DB) outflows produced as large-scale impinging jets and ABL winds. Most experimental, numerical and analytical models in the literature neglect this flow interplay or treat it in an oversimplistic manner through a vector superposition. We found that the generated near-surface outflow is asymmetric, and a high-intensity wind zone develops at the interface between DB and ABL winds. The time variability of the leading edge of the outflow was investigated by synchronizing all wind measurements across the testing chamber. The three-dimensional flow structure was studied using a refined grid of Cobra probes that sampled the flow at high frequencies. The passage of the primary vortex produced a significant decrease in the height of maximum radial wind speed, predominantly in the ABL-streamwise direction. The turbulence intensity was the highest in the region where DB propagates into oppositely directed ABL winds.